A STUDY TO HEALTH ASPECT OF THE BUILDING OF â€œPENDIDIKAN TEKNIK BANGUNAN FKIP PALANGKA RAYA UNIVERSITYâ€ - Wiratno (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This research objective is investigates health aspect of the building of Program Studi Pendidikan Teknik Bangunan, FKIP Universitas Palangka Raya according to Indonesian Article of Peraturan Menteri PU No. 29/PRT/M/2006 concerning Principal of the Technical Requirement of Civil Building. This research is arranged by main data which collected from field investigation. The main stages of this research consist of collecting data and processing. Data of physical building complete with facilities condition are compared to health aspect requirement by the required facilities by the Peraturan Menteri PU No. 29/PRT/M/2006. Based on its analysis result, the physical building complete with facilities condition have been not fully complying requirement of Peraturan Menteri PU No. 29/PRT/M/2006. There is 1 of 4 requirements of the health requirement not complying, especially sanitation requirement. It is important to renovate its building condition, especially sanitation installation. And the most important point to be arranged are a regularly maintenance to its building facilities.